Situation Report: Romania, 20 November 1963 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania Votes for Nuclear-Free Zone in Latin America SED Delegation to Romania Romanian-Yugoslav Trade Talks Reaction to Barghoorn Case Delegation of Consumer Cooperatives to Peking [Beijing] New Bulgarian Ambassador